(untitled) (Bangladesh Journal of Botany, 2023)
The bacterial strain TG6 was screened from the soil of a muskmelon greenhouse, which could effectively inhibit the growth of Sphaerotheca fuliginea, Fusarium oxysporum, Phytophthora melonis and Pseudoperonospora cubensis of muskmelons. TG6 was identified as Bacillus subtilis through morphological, physiological, biochemical and molecular studies. Taking TG6 as the original strain, TG67 and TG69 were obtained by He-Ne laser mutagenesis. The microbial compound antagonist strain TG67 and TG69 was prepared in the ratio of 1:1 and applied to the biological control of greenhouse melon. Muskmelon field experiments showed that the bactericide could effectively control the occurrence of various diseases of muskmelon in greenhouse. Bangladesh J. Bot. 52(4): 1047-1053, 2023 (December)